Емотивні прикметники негативної семантики в англійськомовній картині світу - Melnychuk, Natalia (Видавничий дім «Гельветика», 2021)
The research is devoted to the study of the peculiarities of linguistic presentations of emotional states with the help of adjectives in the English lingual worldview. The paper offers a study of the semantic features of English adjectival emotive units of negative semantics, characterizes the main groups and performs a comparative analysis according to their semantic content. The purpose of this research is to investigate the semantic features of emotional adjectival units of negative semantics in the English lingual worldview. The adjectival emotional units that are the material of this exploration were separated according to the purpose of the study – the study of their semantic features – from the general vocabulary of adjectives of the modern English linguistic dictionaries with the help of definitional and componential analysis. The nature of an adjective presupposes the possibility of its study from the point of view of the subject who chooses one feature from many when choosing an adjective (especially emotional adjectives) that have independent emotional meaning, expressing emotions, feelings and evaluation of the surrounding reality. And since the dictionary reflects a complex lexical system of language as a set of interconnected units (united by the principle of hierarchy) its definitions meet many requirements, the most important of which are the exhaustive definition and consideration of semantical, grammatical and lexical properties of the word (its linguistic and system specifics).The scientific novelty of the obtained results consists in a contrastive analysis of the semantic features of English adjectival units of negative semantics with their division into groups based on the presence of common emosemes in their semantics. The differentiation of emotional adjectives into groups of words with a negative meaning reflects the peculiarities of their functioning in the English lingual worldview: adjectival emotive adjectives of negative semantics make a significant part of the general vocabulary of English and are its important component.
EMOTIVE ADJECTIVES OF NEGAVIVE SEMANTICS IN THE ENGLISH LINGUAL WORLDVIEW
Keywords: семантика; емосема; ад’єктивний емосемізм; емоція; конотація; мовна картина світу; semantics; emoseme; emotive adjective; emotion; connotation; lingual worldview